Dry Land Management Using Agroforestry Systems In Trenggalek Regency, East Java - Susanto, Anang; Harahap, Arman; Julissa Ek-Ramos, Maria (International Journal of Science and Environment (IJSE), 2024)
Dryland management with an agroforestry system is essential and urgent. Currently, the existence of forests has experienced pressure on forest areas and forest resources, which threatens the integrity of forest areas due to the increase in land area, which is categorized as dry. This research aims to determine the size of ​​dry land and the dominant factors that drive the damage rate. This research aims to analyze agroforestry systems with cropping patterns on dry land. This research uses survey, analysis, and needs analysis methods of decent living. Results The agroforestry system used to develop critical land is a human effort to control its reciprocal relationship with natural resources, with the hope that expanding the use of dry land by implementing a directed and planned agroforestry system for the people can improve the economy of the people around the primary forest which is based on forest products. The development of dry land management with an agroforestry system in community forest areas as a result of reforestation and forest development project activities from an institutional aspect is also able to foster farmer innovation in increasing the productivity of their land, one of which is the success of building community forests as a group on marginal land.